ADMET, drug-likeness analyses of N-cyclohexylacrylamide: a first study on molecular docking and dynamic with DAPK1 and associated proteins - Nevin Çankaya; Serap Yalçın Azarkan (Discover Applied Sciences)
Abstract Death-associated protein kinase 1 (DAPK1) is a calcium/calmodulin (Ca2+/CaM)-dependent serine/threonine kinase that acts as a tumor suppressor and controls tumor growth in the early stages. However, its role in promoting tumor epithelial-mesenchymal transition (EMT) and stem cell expression becomes particularly significant in advanced-stage cancers, such as colon and thyroid cancer. The inhibition of DAPK1 might be beneficial to treat cancer. Our research focused on creating a first-in-class, small-molecule DAPK1 inhibitor for cancer therapy. In the present study, we have used a synthesized molecule, N-cyclohexylacrylamide (NCA), to identify DAPK1 and associated protein groups. We obtained the 3D protein structures from the protein data bank. Furthermore, ADMET and drug-likeness properties of the compound were analyzed by using the rules of Lipinski, Veber, and Ghose ( http://www.swissadme.ch/ ). In addition, molecular docking analyses were performed with DAPK1 and related other proteins. In addition, molecular docking and dynamic analyses were performed with DAPK1 and related other proteins. The obtained results showed that NCA would be used in drug development for various diseases.